2004
DOI: 10.1167/iovs.03-0351
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Affects the Junctional Integrity of Retinal Pigment Epithelial Cells

Abstract: Increased resistance to chronic oxidative stress with differentiation in ARPE-19 cells correlated with higher steady state levels of Hsp27 and Hsp70. Oxidative stress disrupted RPE cell junction and barrier integrity, which may contribute to the pathogenesis of diseases related to RPE through disruption of the blood-retinal barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
158
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(175 citation statements)
references
References 29 publications
16
158
0
1
Order By: Relevance
“…It should be noted that the highly differentiated RPE cells (Fig. 6B) are more resistant to TBHP oxidative damage, consistent with what has been reported previously (32).…”
Section: Sulindac Protection Of Rpe Cells Involves Both Mitochondrialsupporting
confidence: 91%
“…It should be noted that the highly differentiated RPE cells (Fig. 6B) are more resistant to TBHP oxidative damage, consistent with what has been reported previously (32).…”
Section: Sulindac Protection Of Rpe Cells Involves Both Mitochondrialsupporting
confidence: 91%
“…Accordingly, PG-mediated regulation of phagocytotic activity may be involved in the mechanism of Trx-and GGA-mediated protection of phagocytotic activity against oxidative stress. Because the levels of Hsp72 contribute to the increased resistance to H 2 O 2 -mediated cell damage in cultured RPE cells (Bailey et al, 2004), and because Hsp72 is stimulated in macrophages that are actively engaged in phagocytosis (Kantengwa and Polla, 1993), Hsp72 induced in the RPE may be involved in GGA-mediated protection of phagocytotic activity against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that doses of up to 1 mM are not cytotoxic, and do not lead to disruption of barrier function in these cells (19). After treatment with H 2 O 2 , monolayers were immediately exposed to 25% NHS as a source of complement proteins (18).…”
Section: Methodsmentioning
confidence: 99%
“…These monolayers exhibit stable transepithelial resistance of ϳ40 -45 ohm/ cm 2 ; are polarized; and stain for markers of tight and adherence junctions (19). In addition, the Cheetham group has shown that ARPE-19 cells when grown as monolayers, are resistant to oxidative damage; while subconfluent ARPE-19 cells exposed to oxidative stress (Ն0.1 mM H 2 O 2 ) undergo apoptosis (20), those grown in monolayers show no sign of damage up to 0.5 mM (19). The earliest sign of damage occurs with H 2 O 2 concentrations above 1 mM, resulting in a reduction of transepithelial resistance (TER) (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation